The Application of Photodynamic Treatment in Dental Specialties (International Journal of Food and Nutritional Sciences, 2022)
Background: The development of science and technology in the medical field opens up opportunities for incorporating novel therapeutic approaches to address the problems posed by prevalent diseases. The growing usage of lasers in dentistry and medical is a reflection of the significant advancements in this technology over the past few decades. A. Mechanical periodontal debridement continues to be the gold standard for the nonsurgical treatment of periodontal disease. It is necessary to often maintain the mechanical periodontal treatment with different anti-infectious agents, such as antiseptics or antibiotics. The periodontal infections are further suppressed by antimicrobial drugs administered locally or systemically, which enhances the advantages of traditional mechanical therapy. The use of antimicrobials is restricted by the growth of resistant microbes and a change in the microbiota after prolonged use. This laid the groundwork for the development of photodynamic therapy and our current use of chemotherapy. For photodynamic antibacterial chemotherapy (PACT), the mouth cavity is particularly well-suited because of its relative accessibility to light. The terms photodynamic therapy, periodontal therapy, photosensitizer, wound healing, laser, and photo dentistry were used in the search to find original research publications, reviews, and case reports. Articles from PubMed and Google were retrieved from a chosen electronic database. In order to treat oral biofilms, a unique therapeutic strategy called photodynamic therapy is presented in this paper.